Why do Europeans Work Less than Americans? Public Consumption and Welfare Benefits as a Cause of the North-Atlantic Divide - Axel Hall; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2015)
We propose an explanation of why Europeans choose to work fewer hours than Americans and also suffer higher rates of unemployment. Labor market regulations, unemployment benefits, and high levels of public consumption in many European countries reduce, ceteris paribus, the gains from being employed, which makes employed workers ask for higher wages relative to productivity. The higher wages make firms offer fewer vacancies, as well as raising the opportunity cost of working by enabling employed workers to enjoy time-consuming consumption activities. We find empirical support for our thesis.
Keywords: J63; J64; J65; 330; job search; unemployment; working hours